2022
DOI: 10.1021/acsomega.2c03479
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Cyclin-Dependent Kinase 6 by Taurine: Implications in Anticancer Therapeutics

Abstract: Cyclin-dependent kinase 6 (CDK6) is linked with a cyclin partner and plays a crucial role in the early stages of cancer development. It is currently a potential drug target for developing therapeutic molecules targeting cancer therapy. Here, we have identified taurine as an inhibitor of CDK6 using combined in silico and experimental studies. We performed various experiments to find the binding affinity of taurine with CDK6. Molecular docking analysis revealed critical residues of CDK6 that are involved in taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…Overexpression of p21 in OC cells mimicked taurine-induced inhibition of proliferation, further supporting the idea that taurine could potentially provide a strategy to inhibit OC cell proliferation through the activation of a major cell-cycle inhibitory pathway. Our data are consistent with recent in silico and cell-free biochemical studies 56 demonstrating that taurine can directly bind cyclin-dependent kinase 6 (CDK6). This interaction appears to inhibit CDK6 activity in solution, supporting the possibility that intracellular taurine accumulation could directly suppress CDK6/Cyclin D activity and arrest the cell cycle in G1 (demonstrated by our data).…”
Section: Discussionsupporting
confidence: 92%
“…Overexpression of p21 in OC cells mimicked taurine-induced inhibition of proliferation, further supporting the idea that taurine could potentially provide a strategy to inhibit OC cell proliferation through the activation of a major cell-cycle inhibitory pathway. Our data are consistent with recent in silico and cell-free biochemical studies 56 demonstrating that taurine can directly bind cyclin-dependent kinase 6 (CDK6). This interaction appears to inhibit CDK6 activity in solution, supporting the possibility that intracellular taurine accumulation could directly suppress CDK6/Cyclin D activity and arrest the cell cycle in G1 (demonstrated by our data).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, by in silico analysis, fluorescence studies, and enzyme inhibition assay, they represented molecule 113 as a promising candidate against cancer (Baig et al, 2022). Yousuf et al (2022) identified taurine (114) (Fig. 24) as a potential CDK6 inhibitor using combined in silico and experimental studies.…”
Section: Cyclin-dependent Kinase 4 (Cdk4)mentioning
confidence: 99%
“…This result was further confirmed by fluorescence measurement studies for the CDK6-114 complex. Enzyme inhibition assay showed the IC 50 value of 4.44 μM, and isothermal titration calorimetric analysis indicated the spontaneous binding of taurine with CDK6 (Yousuf et al, 2022). Lotlikar et al (2021) synthesized and characterized 10 Schiff's bases of 2,7-diamino-2′-oxospiro [chromene-4,3′-indoline]-3-carbonitrile.…”
Section: Cyclin-dependent Kinase 4 (Cdk4)mentioning
confidence: 99%
“…The surface area contributions quantify the change in solvent-accessible surface area (SASA) upon ligand binding, considering alterations in hydrophobic and polar interactions. By combining these components, MM/GBSA provides a comprehensive approach for predicting and analyzing the binding free energies of protein-ligand complexes [39][40][41][42].…”
Section: 7molecular Mechanics/generalized Born Surface Areamentioning
confidence: 99%